Pilot-Scale Operation of a Concrete Sludge Recycling Plant and Simultaneous Production of Calcium Carbonate. Issue 1 (2nd January 2017) - Iizuka, Atsushi; Sasaki, Takeshi; Honma, Masato; Yoshida, Hiroyuki; Hayakawa, Yasuyuki; Yanagisawa, Yukio; Yamasaki, Akihiro
Abstract : A pilot-scale plant to treat concrete sludge and produce calcium carbonate (CaCO3 ) and an environmental purification agent (phosphorus adsorbent derived from concrete sludge, PAdeCS®) was designed, constructed, and operated. Concrete sludge from a concrete pile and pole production plant, boiler gas containing CO2, and groundwater were used in the plant. The process involved calcium extraction from concrete sludge into water, followed by reaction of the calcium with CO2 to produce crystalline CaCO3 . The pilot-scale plant was operated for 1 week, and the mass flows, conversion of CO2 to CaCO3, and net CO2 emissions of the process were estimated. High-purity CaCO3 (>97%) suitable for industrial use was obtained. Based on the power consumption of the process and the amount of CO2 sequestered into CaCO3, a net reduction in CO2 emissions can be achieved using this process. The produced PAdeCS can be used as an inexpensive substitute for calcium series environmental purification agents.